ADHD - New Directions in Diagnosis and Treatment 2015
DOI: 10.5772/60955
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life (QoL) in Attention Deficit Hyperactivity Disorder (ADHD)

Abstract: Abstract"ttention-deficit/hyperactivity disorder "DHD is a neurodevelopmental disorder characterized by inattention, impulsivity, and hyperactivity of core symptoms, affecting -% of school age children, as well as % of adults.Quality of Life QoL is an individual perception in regard to his/her position in life, in the context of culture and value systems in which they live, and in relation to their goals, expectations, standards and concerns. Then it has a multidimensional concept, the core of which consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 89 publications
1
2
0
3
Order By: Relevance
“…This corresponds with previous findings in numerous studies (e.g. Baldwin et al, 2001; Das et al, 2012; Estevez et al, 2014; Gudjonsson et al, 2009; Oerbeck et al, 2015; Vogel et al, 2018; for reviews, see Agarwal et al, 2012; Uneri et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This corresponds with previous findings in numerous studies (e.g. Baldwin et al, 2001; Das et al, 2012; Estevez et al, 2014; Gudjonsson et al, 2009; Oerbeck et al, 2015; Vogel et al, 2018; for reviews, see Agarwal et al, 2012; Uneri et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Adult ADHD has been associated with reduced quality of life (QoL), lower productivity, and increased health care use in numerous clinical and population studies (Agarwal, Goldenberg, Perry, & IsHak, 2012; Uneri, Senses-Dinc, & Goker, 2015). Population studies have shown that even subclinical ADHD symptoms were associated with poorer QoL (Das, Cherbuin, Butterworth, Anstey, & Easteal, 2012; Estevez et al, 2014; Gudjonsson, Sigurdsson, Smari, & Young, 2009; Oerbeck et al, 2015; Vogel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, college students with ADHD have a lower quality of life than do students without ADHD [ 8 ]; they have been shown to be more depressed and anxious, to be more easily angered or to suppress emotion, to have achieve less academically, and to be poorly supported in their relationships with their friends [ 9 , 10 ]. ADHD symptoms have a negative impact on many aspects of life, including self-esteem, academic functioning, social functioning, and parent–child relationships [ 8 , 11 , 12 ]. Adults with ADHD are vulnerable to addiction; ADHD is often accompanied by addictive disorders [ 13 ] that are closely associated with sleep problems, leading to impairment in daily life [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bu durum çocuğun günlük aktivitelerini etkili biçimde sürdürme kapasitesini azaltarak yaşam kalitesini olumsuz etkilemektedir. 6 Yaşam kalitesi kavramı, sağlığın geliştirilmesi ve iyileştirilmesi sürecine geçildiği günümüzde yaşam koşullarının araştırılması, etkileri ve sonuçları bakımından giderek artan bir öneme sahiptir. 7 Bu nedenle yaşam kalitesini değerlendirme, özellikle DEHB gibi yaşamın neredeyse her alanında güçlük çekilen bu hastalıkta, daha fazla önem taşımaktadır.…”
Section: Introductionunclassified
“…Yapılan literatür taramasında DEHB olan çocukların yaşam kalitesini ele alan çalışmaların sınırlı olduğu görülmektedir. 6,9,10…”
Section: Introductionunclassified